Effect of increasing urea level in protein supplements on intake and digestion of low-quality tallgrass-prairie forage by beef steers - Kster, H.H.; Cochran, R.C.; Vanzant, E.S.; St Jean, G.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally fistulated steers were used to evaluate the effect of changing the proportion of supplemental degradable intake protein (DIP) derived from urea on forage intake and digestion. Steers had ad libitum access to a low-quality tallgrass-prairie hay. Supplemental treatment groups were: 1) 0% of the supplemental DIP from urea, 2) 20% of the supplemental DIP from urea, and 3) 40% of the supplemental DIP from urea. Supplements were formulated to contain 30% CP and were fed with prairie hay once daily. Results from this study indicated that urea can replace up to 40% of the supplemental DIP without affecting forage intake and digestion.
Keywords: Beef; Steers; Forage; Nonprotein nitrogen; Intake; Digestibility